Continuously observed light absorbing impurities in snow cover over the southern Altai Mts. in China: Concentrations, impacts and potential sources. (1st February 2021) - Zhong, Xinyue; Kang, Shichang; Zhang, Wei; Yang, Junhua; Niu, Hewen; Liu, Yajun; Guo, Junming; Li, Xiaofei; Chen, Pengfei; Wang, Xiaoxiang
Abstract: The deposition of light absorbing impurities (LAIs) (e.g., black carbon (BC), organic carbon (OC), mineral dust (MD)) on snow is an important attribution to accelerate snowmelt across the northern Xinjiang, China. At present, there is still a lack of understanding of the LAIs concentration, elution and enrichment process in snow cover over Xinjiang. Based on these, continuously sampling during two years carried out to investigate the concentrations, impacts and potential sources of LAIs in snow at Kuwei Station in the southern Altai Mountains. The average concentrations of BC, OC and MD in the surface snow were 2787 ± 2334 ng g −1, 6130 ± 6127 ng g −1, and 70.03 ± 62.59 μg g −1, respectively, which dramatically increased along with snowmelt intensified, reflecting a significant enrichment process of LAIs at the snow surface. Besides, high LAIs concentrations also found in the subsurface and melting layers of the snowpit, reflecting the elution and redistribution of LAIs. With the simulation of the SNow ICe Aerosol Radiative model, BC was the main dominant factor in reducing snow albedo and radiative forcing (RF), its impact was more remarkable in the snowmelt period. The average contribution rates of BC, MD and BC + MD to snow albedo reduction increased by 20.0 ± 1.9%, 13.0 ± 0.2%, and 20.5 ± 2.3% in spring compared with that in winter; meanwhile, the corresponding average RFs increased by 15.8 ± 3.4 W m −2, 4.7 ± 0.3 W m −2 and 16.4 ± 3.2 W m −2, respectively. Changes in the number of snowmelt days caused by BC and MD decreased by 3.0 ± 0.4 d to 8.3 ± 1.3 d. It indicated that surface enrichment of LAIs during snow melting might accelerate snowmelt further. Weather Research and Forecasting Chemistry model showed that the resident emission was the main potential source of BC and OC in snow. This implied that the mitigation of intensive snowmelt needs to mainly reduce resident emission of LAIs in the future. Graphical abstract: Image 1 Highlights: Light absorbing impurities (LAIs) in snowpit were analyzed in the Altai Mountains. A significant enrichment process of LAIs appeared on snow surface. Black carbon (BC) had a greater role in snow albedo, radiative forcing and snowmelt than mineral dust. Residential emission was the main source of BC and organic carbon deposited on snow. Abstract : Capsule: Vertical variations and enrichment process of LAIs concentrations in snowpit were analyzed in the southern Altai Mountains.